2018
DOI: 10.1007/s00299-018-2304-7
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of gene encoding the key enzyme involved in proline-biosynthesis (PuP5CS) to improve salt tolerance in switchgrass (Panicum virgatum L.)

Abstract: Genetic improvement through overexpressing PuP5CS in switchgrass is feasible for enhancing plant salt stress tolerance. Switchgrass (Panicum virgatum L.) has developed into a dedicated bioenergy crop. To improve the biomass production of switchgrass grown on different types of soil, abiotic stress tolerance traits are considered for its genetic improvement. Proline accumulation is a widespread response when plants are subjected to abiotic stresses such as drought, cold and salinity. In plants, P5CS gene encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 54 publications
3
22
1
Order By: Relevance
“…In our study, the contents of O 2− and H 2 O 2 in H559 were significantly lower than YM21 under both normal and low temperatures, and the H 2 O 2 content in H559 showed a reduction trend, indicating that the tolerant variety could restrict the accumulation of ROS in the cold. Under abiotic stress, various osmoregulatory substances such as soluble sugars (SS) and soluble proteins (SP) accumulate rapidly to enhance plant stress resistance [44,48]. Before and within 24 h of cold stress, the intracellular SS and SP concentrations of cold-sensitive variety were consistently and significantly higher than that of tolerant variety, which was similar to previous studies [41,49].…”
Section: Physiological Response Of Cotton Cotyledons To Chilling Stresssupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, the contents of O 2− and H 2 O 2 in H559 were significantly lower than YM21 under both normal and low temperatures, and the H 2 O 2 content in H559 showed a reduction trend, indicating that the tolerant variety could restrict the accumulation of ROS in the cold. Under abiotic stress, various osmoregulatory substances such as soluble sugars (SS) and soluble proteins (SP) accumulate rapidly to enhance plant stress resistance [44,48]. Before and within 24 h of cold stress, the intracellular SS and SP concentrations of cold-sensitive variety were consistently and significantly higher than that of tolerant variety, which was similar to previous studies [41,49].…”
Section: Physiological Response Of Cotton Cotyledons To Chilling Stresssupporting
confidence: 87%
“…However, molecular mechanisms of plant responses and resistance to different temperature stresses are usually different [42]. To cope with cold stress, plants have evolved many strategies to help them survive and maintain growth, such as keeping ROS balance and accumulating osmotic substances [43,44]. In plants, ROS include hydrogen peroxide (H 2 O 2 ), singlet oxygen, and superoxide anions, and their levels in cells are usually regulated by various antioxidant enzymes, such as CAT, POD, and SOD [45].…”
Section: Physiological Response Of Cotton Cotyledons To Chilling Stressmentioning
confidence: 99%
“…These results indicate that proline generates the suppression of NaCl-induced physiological damage as shown by the lower electrolyte leakage and ROS levels which further explain that proline significantly improves the physiological status of stressed plants (Figures 4 and 6). Similarly, our previous results also showed that overexpressing heterologous P5CS genes from Lolium perenne and Puccinellia chinampoensis in switchgrass improve the salt tolerance by reducing the electrolyte leakage and ROS levels (Guan et al, 2018;Guan et al, 2019). Therefore, no matter overexpressing heterologous or endogenous P5CS genes in switchgrass, which can increase the proline content and improve the salt stress.…”
Section: Function Of Pvp5cs1 and Pvp5cs2 In Switchgrassmentioning
confidence: 52%
“…For example, compared with sensitive ones, the salt-tolerant genotypes of grass crops including maize (Richter et al, 2015), rice (Boriboonkaset et al, 2013), and wheat (Kerepesi and Galiba, 2000) have high soluble sugar content. Also, overexpression of the proline biosynthesis enzyme gene P5CS increases the proline accumulation, which leads to improving salt tolerance in switchgrass (Guan et al, 2018). Here, the zmcps-1 and zmcps-7 plants both showed higher soluble sugar and proline content than the WT maize under salt stress.…”
Section: Discussionmentioning
confidence: 89%
“…For example, plants can synthesize compatible osmolytes such as proline and soluble sugars to adjust cell water potential and keep membrane potential and stability under salt-induced osmotic stress (Apse and Blumwald, 2002;Szabados and Savoure, 2010;Guo et al, 2015). Overexpression of the proline biosynthesisrelated gene delta 1-Pyrroline-5-Carboxylate Synthetase (P5CS) improves salt tolerance in grass plants (Guan et al, 2018). Meanwhile, high Na + concentration in cytosol is harmful to plant growth, and maintaining a suitable cellular Na + /K + homeostasis is critical to prevent cell damage and metabolic inhibition (Serrano et al, 1999).…”
Section: Introductionmentioning
confidence: 99%